THE SYSTEM OF GREEN CERTIFICATES - PROMOTER OF ENERGY FROM RENEWABLE RESOURCES - PĂVĂLOAIA, Leontina; Georgescu, Iuliana (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The traditional economic development aims at customer satisfaction and profits maximization, but overused the natural resources. Therefore, it becomes a necessity to take into account the social and environmental aspects. In order to ensure sustainable development, it have been adopted numerous rules and regulations which set objectives and targets aiming to reduce emissions and contributing to a responsible behavior. One of the objectives set at EU level is to ensure that sustainable development is the use of renewable resources in the production of electricity. In order to encourage the use of renewable energy sources for energy production it applied a system of promotion throughout green certificates, which aims, among other goals, to reduce imports of primary energy resources, stimulate the local and regional sustainable development, create employment throughout new jobs, reduce the environmental pollution by minimizing emissions. In this paper we intend to analyze the tools used in Romania for the purpose of promoting the production of energy from renewable sources, the green certificates market, the share of renewable energy in gross inland consumption, the fulfillment degree of the target and their reflection in the annual financial statements of energy production companies listed on the Bucharest Stock Exchange.